Joint Annual Meeting of GAMM and DMV - Braunschweig 2016 Overview of the Sections (Proceedings in applied mathematics and mechanics, 2016)
Volume 16 (2016) of PAMM “Proceedings in Applied Mathematics and Mechanics” assembles the contributions to the Joint 87th Annual Meeting of the Gesellschaft für Angewandte Mathematik und Mechanik, held 7 – 11 March 2016 at TU Braunschweig, Germany. The contributions are grouped according to the minisymposia and sessions of the conference. Overview of the Sections Minisymposia M 1 Computer algebra M 2 Immersed boundary methods M 3 Linear and multilinear methods for electronic structure calculations M 4 Mechanics and model based control M 5 Space‐time methods for parabolic and hyperbolic PDEs M 6 Robust simulation of mechanical systems with uncertainties M 7 Control of partial differential equations Sections 1–29 1 Multi‐body dynamics 2 Biomechanics 3 Damage and fracture mechanics 4 Structural mechanics 5 Nonlinear oscillations 6 Material modelling in solid mechanics 7 Coupled problems 8 Multiscales and homogenization 9 Laminar flows and transition 10 Turbulence and reactive flows 11 Interfacial flows 12 Waves and acoustics 13 Flow control 14 Applied analysis 15 Applied stochastics 16 Optimization 17 Applied and numerical linear algebra 18 Numerical methods of differential equations 19 Optimization of differential equations 20 Dynamics and control 21 Mathematical signal and image processing 22 Scientific computing 23 Applied operator theory 24 History of fluid mechanics and history, teaching and popularization of mathematics 25 Algebra, logic and set theory 26 Discrete mathematics and theoretical computer science 29 Mathematics in the sciences and technology Young Researchers' Minisymposia YR 1 Multiscale evolutionary problems YR 2 Mechano‐regulated growth and remodeling in biological tissues YR 3 Dedicated regularization for variational image processing YR 4 Variational integrators in simulation and control YR 5 Impinging jets Zentralblatt Meeting zbMATH Mathematical research data management